2023
DOI: 10.1021/acsnano.3c01599
|View full text |Cite
|
Sign up to set email alerts
|

Remote Activation of Enzyme Nanohybrids for Cancer Prodrug Therapy Controlled by Magnetic Heating

Beatriz Torres-Herrero,
Ilaria Armenia,
Maria Alleva
et al.

Abstract: Herein, we have developed nanohybrids (nHs) to remotely activate a therapeutic enzyme for its use in Directed Enzyme Prodrug Therapy (DEPT). The coencapsulation of magnetic nanoparticles (MNPs) with horseradish peroxidase (HRP) using biomimetic silica as an entrapment matrix was optimized to obtain nanosized hybrids (∼150 nm) for remote activation of the therapeutic enzyme. HRP converts indole-3-acetic acid (3IAA) into peroxylated radicals, whereas MNPs respond to alternating magnetic fields (AMFs) becoming lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…To evaluate the magnetic hyperthermia properties of Fe 3 O 4 and Fe 3 O 4 @Bi 2 S 3 nanospheres, the Fe 3 O 4 and Fe 3 O 4 @Bi 2 S 3 solutions (2 mL) with different concentrations were placed into a 5 mL insulated cryopreservation tube and placed inside the middle of the copper coil to apply an alternating magnetic field (AMF) (390 kHz, 18 A). The specific absorption rate (SAR) was employed to evaluate the magnetic hyperthermia efficiency captured per unit time . Infrared thermographic images showed that the Fe 3 O 4 and Fe 3 O 4 @Bi 2 S 3 groups emerged with a significant magnetothermal heating effect compared to the PBS group (Figure a) within 600 s of AMF.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the magnetic hyperthermia properties of Fe 3 O 4 and Fe 3 O 4 @Bi 2 S 3 nanospheres, the Fe 3 O 4 and Fe 3 O 4 @Bi 2 S 3 solutions (2 mL) with different concentrations were placed into a 5 mL insulated cryopreservation tube and placed inside the middle of the copper coil to apply an alternating magnetic field (AMF) (390 kHz, 18 A). The specific absorption rate (SAR) was employed to evaluate the magnetic hyperthermia efficiency captured per unit time . Infrared thermographic images showed that the Fe 3 O 4 and Fe 3 O 4 @Bi 2 S 3 groups emerged with a significant magnetothermal heating effect compared to the PBS group (Figure a) within 600 s of AMF.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, plant-derived HRP and human myeloperoxidase (MPO) were observed to promote the oxidation of IAA into IAld. This prompted us to utilize the HRP or MPO genes as queries to search for functionally similar enzymes from the L.…”
Section: Resultsmentioning
confidence: 99%
“…The precise microbial enzymes involved in IAA processing as well as their structure and activities have yet to be described. An early study has shown that plant peroxidases can catalyze the oxidation reaction of IAA to IAld with molecular oxygen . Interestingly, plant peroxidases and bacterial DyPs share some common substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the catalytic metals, thermophilic enzymes can also be interfaced with magnetic NPs to induce non-native biochemical reactions. For example, Torres-Herrero et al synthesized a hybrid nanosystem containing three components: horseradish peroxidase (HRP) as a therapeutic enzyme and magnetic NP clusters as AMF-induced local heaters inside the silica container to employ for directed-enzyme-prodrug-therapy …”
Section: Plasmonic/magnetic Nrs For Reaction Rate Enhancementmentioning
confidence: 99%